Effects of carbon black on epoxidized natural rubber composites: Rheological, abrasion, and mechanical study. (December 2022) - Tareen, Muhammad Humble K; Hussain, Fiaz; Zubair, Zakariya; Aslam, Samina; Saleem, Tahira; Awais, Muhammad; Farooq, Assad; Goda, Ibrahim
A detailed analysis of the rubber composites is necessary for the designing and fabrication of advanced rubber products. In this study, composite materials are synthesized by adding different nanofillers of carbon black nanoparticles into epoxidized natural rubber (ENR). The specific characteristics of carbon black (CB) affect the crosslinking density between CB and polymeric chains in ENR. The effects of particle size, structure, thermal conductivity, and functionality of CB on rheology and mechanical properties of filled reinforced ENR are examined. The composite materials are thoroughly characterized for their abrasion, rheology, tensile, hardness, elongation, resilience, and compression behavior. The results revealed that various properties of composite materials depend on the characteristics of the reinforcing CB fillers. It was found that lower particle size and ordered structure provide good tensile strength, tear strength, abrasion, and aging resistance. In contrast, larger particle size and a lower ordered structure provide high flow rate, low hardness, excellent re-bounce, and good compression set characteristics.